2000
DOI: 10.1128/iai.68.10.5690-5695.2000
|View full text |Cite
|
Sign up to set email alerts
|

Role of Novel Choline Binding Proteins in Virulence of Streptococcus pneumoniae

Abstract: The choline binding proteins (CBPs) are a family of surface proteins noncovalently bound to the phosphorylcholine moiety of the cell wall of Streptococcus pneumoniae by a conserved choline binding domain. Six new members of this family were identified, and these six plus two recently described cell wall hydrolases, LytB and LytC, were characterized for their roles in virulence. CBP-deficient mutants were constructed and tested for adherence to eukaryotic cells, colonization of the rat nasopharynx, and ability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
239
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(247 citation statements)
references
References 34 publications
6
239
0
1
Order By: Relevance
“…Pce belongs to the metallo-b-lactamase family, and structural information provides evidence that only PCho residues that are located at the end of the teichoic acid chains are accessible to the catalytic centre. The ability of Pce to modify the amount of PCho on the cell wall has been shown to be relevant for pneumococcal adherence to human cells and for nasopharyngeal colonization of rats (Gosink et al, 2000). Strikingly, loss of function has also been shown to increase the virulence of pneumococci when inoculated into the peritoneum of mice (Vollmer & Tomasz, 2001).…”
Section: Biological Activities Of Unusually Cell-wallanchored Cholinementioning
confidence: 99%
See 2 more Smart Citations
“…Pce belongs to the metallo-b-lactamase family, and structural information provides evidence that only PCho residues that are located at the end of the teichoic acid chains are accessible to the catalytic centre. The ability of Pce to modify the amount of PCho on the cell wall has been shown to be relevant for pneumococcal adherence to human cells and for nasopharyngeal colonization of rats (Gosink et al, 2000). Strikingly, loss of function has also been shown to increase the virulence of pneumococci when inoculated into the peritoneum of mice (Vollmer & Tomasz, 2001).…”
Section: Biological Activities Of Unusually Cell-wallanchored Cholinementioning
confidence: 99%
“…A role in colonization has been suggested for CbpD and CbpG, which are thought to be serine proteases (Gosink et al, 2000). Recent reports indicate that CbpD is a competence-stimulating-peptide-inducible protein, and a function as a murein hydrolase has been proposed.…”
Section: Biological Activities Of Unusually Cell-wallanchored Cholinementioning
confidence: 99%
See 1 more Smart Citation
“…We found that despite its relatively small genome, TM7x contains many pathogenesis-related virulence gene homologs, including two virulence islands encoding separate type IV secretion systems and membrane-associated virulence-related proteins, such as OmpA (36) and LemA (37), as well as cholinebinding proteins (38) (Table S2). It is particularly interesting to point out that the TM7x genome contains various ORFs encoding predicted proteins with toxin-antitoxin (TA) domains, such as VapC, VapB, and xenobiotic response element (39), as well as an abortive infection protein homolog known to promote cell death and limit phage replication within a bacterial population (40).…”
Section: Conserved Gene Synteny But Further Genome Reduction Is Evidementioning
confidence: 99%
“…This domain facilitates attachment to multiple choline head units of the teichoic and lipoteichoic acids that are found throughout the pneumococcal cell wall (Brundish & Baddiley, 1968;Tomasz, 1967) and is comprised of a highly conserved $20-amino-acid repeat with between two and ten repeats forming the domain (Yother & White, 1994). Members of the family show diverse functionality and are often strongly implicated in organism virulence (Gosink et al, 2000). There are also several family members for which no function is available and no sequence similarity exists and these may also be important pneumococcal virulence factors.…”
Section: Introductionmentioning
confidence: 99%